2021
DOI: 10.4018/ijicte.2021010102
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Inescapable Suffering Among Postgraduate Researchers

Abstract: This study aims to get a deep understanding of the causes, effects, and remedies of information overload (IO) phenomenon among postgraduate scholars in the era of advanced internet technology. In-depth semi-structured face-to-face interviews and focus group interviews were implemented. Majority of the participants in this study exposed that IO represents real inescapable suffering that severely affects their research performance in different stages of their research. Time-consuming, cost, inferior research wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…Information overload, diartikan sebagai keadaan dimana individu menjadi kesulitan dalam memahami suatu isu dan mengambil kebijakan karena adanya informasi yang berlebih. "Information overload was the environmental source represented through the school's lack of standardized research guidance, structured courses, training, and well-planned research process orientation" (Al-Kumaim et al, 2021). Akibat respon dari yang tidak cakap dalam mengelola informasi, maka dengan adanya information overload dapat menyebabkan manusia dalam kebingungan.…”
Section: Pendahuluanunclassified
“…Information overload, diartikan sebagai keadaan dimana individu menjadi kesulitan dalam memahami suatu isu dan mengambil kebijakan karena adanya informasi yang berlebih. "Information overload was the environmental source represented through the school's lack of standardized research guidance, structured courses, training, and well-planned research process orientation" (Al-Kumaim et al, 2021). Akibat respon dari yang tidak cakap dalam mengelola informasi, maka dengan adanya information overload dapat menyebabkan manusia dalam kebingungan.…”
Section: Pendahuluanunclassified
“…However, predatory publishing and fake academic conferences can subject academic papers to irrelevance (Taylor, 2019). In addition, factors that contribute to the struggles of publishing also involve the personal issues of postgraduate researchers, such as poor physical and mental health (Al-Kumaim et al, 2021). Data from several studies revealed that feelings of discomfort and fear of rejection concerning the high expectations of their mentors, as well as commitment issues with their personal life and non-curricular responsibilities, are also barriers for postgraduate researchers to work on their research output (Alvarez et al, 2014;Bocar, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…IO has been extensively researched in various contexts, as reviewed by Bawden and Robinson (2020), Edmunds and Morris (2000), Khaleel et al (2020), and Roetzel (2019). In work and study settings, IO is known to diminish efficiency, productivity, and performance (Al-Kumaim et al, 2021;Benselin and Ragsdell, 2016). When individuals experience information overload, information that could potentially be useful turns into a hindrance (Bawden et al, 1999;Stanley, 2021).…”
Section: Introductionmentioning
confidence: 99%